Puf4 -mediated oxidative stress virulence attenuation in Cryptococcus neoformans - Chenhao Suo; Jianjun Lei; Wanli Zhang; Lihui Jia; He Zhang (Frontiers in Cellular and Infection Microbiology)
IntroductionCryptococcus neoformans is a ubiquitous environmental fungal pathogen whose pathogenicity is closely linked to its ability to adapt to host environments. The RNA-binding protein Puf4 plays a key role in regulating the cell wall of C. neoformans. However, the specific mechanisms by which Puf4 regulates metabolism and virulence remain unclear.MethodsIn this study, we systematically investigated the role of Puf4 in the metabolism and virulence of C. neoformans using RNA sequencing (RNA-seq), biochemical analysis, and in vivo animal experiments.ResultsColony-spotting assay assays show that Puf4 affects the cell membrane and oxidative stress. RNA-seq analysis revealed that Puf4 was enriched in key metabolic pathways, including carbohydrate metabolism, oxidative phosphorylation, and glycolysis. Biochemical analysis revealed that Puf4 overexpression led to significant increases in both total carbohydrate and glycogen content. Additionally, the Puf4-overexpressing strain showed elevated ROS levels, and reduced resistance to antimycin A, indicating decreased oxidative stress tolerance. Notably, Puf4 overexpression resulted in reduced capsule size and decreased L-DOPA production, accompanied by downregulated expression of the capsule-associated gene CAP10 and the melanin biosynthesis gene LAC1. In vivo animal experiments further confirmed that the virulence of the Puf4-overexpressing strain was significantly attenuated.DiscussionThese findings suggest that Puf4 may serve as a regulator linking metabolic status and pathogenic potential in C. neoformans, although the underlying mechanisms require further elucidation.